The clinical impact of cirrhosis on the postoperative outcomes of patients undergoing bariatric surgery: propensity score-matched analysis of 2011-2017 US hospitals. (3rd October 2021) - Lee, David Uihwan; Fan, Gregory Hongyuan; Hastie, David Jeffrey; Addonizio, Elyse Ann; Prakasam, Vibhav Narayan; Ahern, Ryan Richard; Suh, Julie; Seog, Kristen Jin; Karagozian, Raffi
ABSTRACT: Objectives : Since there is increasing number of patients with cirrhosis who require the bariatric procedure due to obesity and obesity-related nonalcoholic steatohepatitis fibrosis, we evaluate the effect of cirrhosis on post-bariatric surgery outcomes. Methods : 2011–2017 National Inpatient Sample was used to isolate bariatric cases, which were stratified by cirrhosis; controls were propensity-score matched to cases and compared to endpoints: mortality, length of stay (LOS), costs, and postoperative complications. Results : From 190, 753 patients undergoing bariatric surgery, there were 957 with cirrhosis and 957 matched controls. There was no difference in mortality (0.94 vs 0.52% p = 0.42, OR 1.81 95%CI 0.60–5.41); however, cirrhosis patients had higher LOS (3.36 vs 2.89d p = 0.002), costs ($68, 671 vs $61, 301 p < 0.001), and bleeding (2.09 vs 0.72% p < 0.001, OR 2.95 95%CI 1.89–4.61). In multivariate, there was no difference in mortality (p = 0.330, aOR 1.73 95%CI 0.58–5.19). In subgroup comparison of cirrhosis patients, those with decompensated cirrhosis had higher mortality (7.69 vs 0.94% p < 0.001, OR 8.78 95%CI 3.41–22.59). Conclusion : The results of this study show compensated cirrhosis does not pose an increased risk toward post-bariatric surgery mortality; however, hepatic decompensation increases the postsurgical risks.